Implications for the European Union of the May 2008 draft agricultural modalities - Jean, Sébastien; Josling, Timothy Edward; Laborde Debucquet, David (International Centre for Trade and Sustainable Development, 2008)
To what extent would a successful conclusion of the Doha Development Agenda (DDA), along the lines of the modalities in the Revised Draft Modalities paper of May 19, 2008, require further changes in the Common Agricultural Policy? Will those changes be made easier by corresponding disciplines on the domestic programs of other countries? How much increased market access is likely to be generated as a result of cuts in tariffs that would be required of the EU? Can the EU expect to expand its own exports of agricultural products as a result of the tariff cuts of others? Will the termination of the EU’s use of export subsidies to balance its internal market have any significant impact on price levels and on world market conditions? And to what extent will the modification of the export policies of competitors help the EU to move away from export subsidies? What other issues will the EU insist on as it moves towards a package that is acceptable to Member States? This paper attempts to address these issues, as a way of exploring the domestic and international implications of a Modalities agreement. The first section of the paper gives some background information on the nature of the CAP as it relates to the disciplines introduced in the URAA. This section is useful to give some perspective on the potential impact of the DDA as it relates to the recent development of the CAP. A second section reviews briefly the main “offensive” and “defensive” positions of the EU, so as to be able to evaluate the extent to which the modalities draft addresses these issues. This perspective is relevant to the political reactions that will determine the acceptability of the Modalities. The next three sections discuss in more detail the implications of the domestic support, market access and export competition modalities, and give an interpretation of the WTO disciplines as a constraint on future policy developments. A final section attempts an overall assessment of the impacts of the suggested modalities on the EU and on its negotiating interests.